La valutazione della performance strategica di una piccola impresa: il caso Bartolucci Francesco S.r.l. - Conti, Emanuela; Pencarelli, Tonino (Piccola Impresa / Small Business, 2011)
This article describes four dimensions of the strategic performance of a small firm of the artistic crafts based in Pesaro: the competitive dimension, the social dimension, the dimension of internal processes, innovation and learning, and the economic and financial dimension. The company’s success is based mainly on the originality and uniqueness of the offer which consists in the intuition, creativity and pragmatism of the entrepreneur and, secondly, on the ability of the entrepreneur to empower employees, to create value for the social actors and to preserve economic and financial balance. The analysis of the case shows that the model proposed, though with simplifications and limitations, allows the management and the ownership of small and medium enterprises to monitor business performance by taking a holistic perspective, highlighting the critical areas of management.